2008
DOI: 10.1007/s11604-007-0188-5
|View full text |Cite
|
Sign up to set email alerts
|

Polypoid endometriosis of the ureter mimicking fibroepithelial polyps

Abstract: We present a case of polypoid endometriosis of the ureter that showed bilateral polypoid intraluminal masses in the lower part of the ureter mimicking ureteral fibroepithelial polyps, arising with a background of pelvic endometriosis and a history of gonadotropin releasing hormone (GnRH) therapy. Magnetic resonance imaging revealed the masses to have high signal intensity on T2-weighted imaging. The location and bilaterality of the polypoid intraluminal masses are considered useful points in the differential d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…[7][8][9][10] Each of these cases consisted of a mass with cystic component containing polypoidal areas that were hyperintense on T 2 -weighted image and demonstrated homogeneous enhancement on contrast study, as in our case. [7][8][9][10] Furthermore, Takeuchi and associates described linear areas of hypointensity contained in the polypoid areas of polypoid endometriosis adjacent to the uterus and rectum on T 2 -weighted image,ˆndings compatible with the site ofˆbrous tissue. 9 In the present case, as in that of Takeuchi's group, T 2 -weighted image revealed the cystic mass with solid component of hyperintense signal with hypointense rim and linear areas (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…[7][8][9][10] Each of these cases consisted of a mass with cystic component containing polypoidal areas that were hyperintense on T 2 -weighted image and demonstrated homogeneous enhancement on contrast study, as in our case. [7][8][9][10] Furthermore, Takeuchi and associates described linear areas of hypointensity contained in the polypoid areas of polypoid endometriosis adjacent to the uterus and rectum on T 2 -weighted image,ˆndings compatible with the site ofˆbrous tissue. 9 In the present case, as in that of Takeuchi's group, T 2 -weighted image revealed the cystic mass with solid component of hyperintense signal with hypointense rim and linear areas (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, Othman et al [11] reported a case of polypoid endometriosis following gonadotrophin-releasing hormone (GnRH) agonist. They postulated that the lesion developed as a rebound phenomenon upon withdrawal of GnRH agonist-induced hormonal suppression [12]. In view of pathological characteristics, Parker et al defined polypoid endometriosis as ''an admixture of benign, but sometimes atypical, appearing endometriotic glands and benign-appearing endometriotic stroma.''…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review using PubMed identified approximately 40 cases of polypoid endometriosis . The mean age was 52.2 years (23–89 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…Ascites was not noted except in one case. Of these 40 cases, MRI pictures in the reports were available in six cases whose predominant sites were the cervix, ovary, uterus, Pouch of Douglas, ureter and bladder (Table ) . Although the signal intensity of the mass on T1‐WI ranged from low to high, T2‐WI showed high signal intensity in four cases, and these masses were enhanced by gadolinium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation